Schistosoma mansoni and Biomphalaria snails in Lake Victoria: distribution, genetics and ecological dynamics - Standley, Claire J. (2011)
Intestinal schistosomiasis, caused by the trematode parasite Schistosoma mansoni, is a disease of major public health importance in the Lake Victoria region. Accurate information pertaining to the disease's distribution can greatly assist in the maintenance and realignment of existing control strategies. Rapid mapping of disease prevalence is reliant on diagnostic technologies; in the case of intestinal schistosomiasis, traditional stool-based methods are beginning to be complimented with new, rapid diagnostic tools. However, these require extensive validation, in a variety of settings, to determine their efficacy and field-utility. Similarly, diagnostic tests are influenced by other factors, such as the level of endemicity of the parasite, or even intraspecific factors such as genetic diversity. Preliminary research has shown S. mansoni to have high levels of genetic diversity throughout East Africa, although its population dynamics within Lake Victoria have never been explored in detail. Local transmission of the parasite is determined by the presence of compatible snails of the genus Biomphalaria. which act as the intermediate host for S. mansoni. As such, basic distribution mapping of the presence and abundance of Biomphalaria around Lake Victoria will better reveal potential risk areas for transmission; these data could also lead to a greater understanding of the specific environmental conditions preferred by Biomphalaria, allowing for predictive mapping of suitable transmission environments. Sophisticated geostatistical tools have facilitated this process, although new, Bayesian models, which have yielded dividends in parasite mapping, have yet to be applied to intermediate host distribution mapping. There is evidence for species-level differences in compatibility with S. mansoni; the taxonomy of Biomphalaria is confused and confusing, with two suspected species being present in Lake Victoria, but these populations have never been subject to detailed classification scrutiny. Similarly, there may be intraspecific effects on transmission compatibility; population level analysis would elucidate patterns of genetic variation across Lake Victoria. Taking both the genetics and ecological preferences of Biomphalaria into consideration, there may be an effect of scale, which should be explored. Patterns that are found to be significant at the level of Lake Victoria may not hold true at a local scale, crucial for the local transmission biology of the parasite. For example, research has suggested that the presence of other gastropods could reduce the abundance of Biomphalaria, through competitive effects. Diversity may influence the transmission of schistosomiasis at the level of the terminal host as well; it is well known that rodents are capable of acting as reservoirs for S. mansoni, as are numerous nonhuman primates. However, within the context of Lake Victoria, non-human primates have rarely been comprehensively surveyed for the disease, despite the obvious implications for conservation, as well as the potential effect on maintaining local transmission cycles even in the face of treatment campaigns. The research presented in the following thesis sought to address the above themes, relating to the dynamics of S. mansoni and Biomphalaria in Lake Victoria. Through a series of four field expeditions to the Ugandan, Tanzanian and Kenyan shorelines of Lake Victoria, data were collected pertaining to the distribution of S. mansoni in school-age children; 27 schools in Uganda were first surveyed for prevalence and intensity of infection. Questionnaires revealed high levels of migration among the school-children, with high levels of itinerancy also associated with increased risk of being infected with S. mansoni and of missing school-based treatment with praziquantel. Later surveys in Tanzania and Kenya compared prevalence of infection as diagnosed by Kato-Katz stool thick smears against a novel, urine-based, rapid diagnostic called the cathodic cirulating antigen (CCA) dipstick. The CCA performed well, with good agreement against the Kato-Katz diagnostic and high sensitivity and specificity in this high-endemicity environment. However, when the CCA tests were used alongside Kato-Katz thick smears in the Ssesse Islands in Uganda, the agreement was not so good, suggesting that different transmission environments may affect the efficacy of diagnostic tests, and moreover, may result in widely discordant treatment recommendations being put forward. Throughout all of these field expeditions, stool samples were also used for hatching of schistosome eggs and miracidia were collected and stored on Whatman® FT A cards for later molecular analysis. Combined with DNA sequences obtained from cercariae from shedding snails and adult worms passaged in the laboratory, genetic material was obtained from 25 sites along the shoreline of Lake Victoria, representative of all three countries. Using both cytochrome oxidase sub-unit 1 (COl) and microsatellite DNA markers, population genetics analyses revealed extremely high genetic diversity, consistent with previous research, but also low levels of population structuring, with no clear geographical patterns. This contrasted with earlier work which had suggested that the populations of S. mansoni ; in Lake Albert and Lake Victoria appeared segregated; the greater and more extensive sampling presented in this thesis revealed a cross-over of haplotypes between the two lakes, potentially associated again with human migration throughout the region, but also suggesting that adaptation and compatibility with local Biomphalaria populations for successful transmission might be less crucial than previously assumed. In order to investigate the distribution and genetics of Biomphalaria, as well as relate these patterns to the transmission of S. mansoni, malacological surveys were carried out at 223 sites across the Lake Victoria shoreline. Two forms of Biomphalaria, based on shell characteristics, were observed; B. sudanica-like snails were commonly associated in marsh-like habitats whereas B. choanomphala-type snails were more usually found in the lake proper. These observations, together with a number of other environmental variables, were statistically tested using multivariate models within a Bayesian inference framework, a method which has never previously been used on snail intermediate host distributions. The models revealed different factors as being Significant predictors of B. sudanica versus B. choanomphala presence, reinforcing the hypothesis of habitat segregation between the two forms. Closer examination of the two forms of Biomphalaria found suggested intermediate shell forms as well as the more easily recognised B. choanomphala-like and B. sudanica-like forms. In order to elucidate the taxonomy of these various forms, a detailed molecular and morphological assessment was carried out on 7 populations of Biomphalaria. Morphologically, principal component analysis (PCA) of shell measurements, aperture outlines and internal anatomy measurements revealed overlapping groupings, supporting the earlier observation of intermediate forms. CrUcially, there were no clear species-level divisions in the genetic data; the groupings that were observed were not significantly associated with those according to morphology. These data combined to imply that the Biomphalaria in Lake Victoria should be considered one species, with two ecophentoypic variants: B. choanomphala var. choanomphala and B. choanomphala var. sudan;ca. Population level analysis of a total of 29 populations revealed significant levels of population structuring with strong geographical patterns; given these local variations, yet also considering the very different patterns observed for S. mansoni, these findings could suggest that local compatibility is less of a restriction on the spread of the parasite than previously thought. At a micro-scale, surveys conducted on Ngamba and Kimi Islands in Uganda, revealed complex patterns of Biomphalar;a genetic structuring mirroring those seen at a lake-wide level. However, the Bayesian statistical models used for predicting the distribution of the snails and their abundance showed a marked difference to the large scale models, with few, if any, significant environmental predictors. The one exception was species diversity; the micro-scale surveys also provided an opportunity to examine closely the gastropod species assemablages on the two islands, and their effect on the abundance of Biomphalaria as well as transmission of S. mansoni. Gastropod species diversity, surprisingly, proved to be a positive predictor of Biomphalaria abundance at a micro-scale, as it had been for Biomphalaria presence throughout Lake Victoria. The role of anthropogenic disturbance on gastropod diversity was also investigated; while human influence did not have a statistically significant effect on species assemblage diversity, more snails (of any genus) were found infected with parasites on Kimi Island, which is characterised by high human and livestock population density. Ngamba Island, on the other hand, is a chimpanzee sanctuary; the micro-scale surveys were followed up by parasitological investigation of children on Kimi island as well as staff and chimpanzees resident on Ngamba Island and found S. manson; in all. Molecular analysis on miracidia hatched from these wild-born, semi-captive chimpanzees, never previously attempted, revealed haplotypes common throughout Lake Victoria, indicating shared or even anthropozoonotic transmission. Snails shedding S. manson; were further found in the waters around Ngamba Island; a later survey also observed a snail shedding S. rodhaini, which is an often-overlooked, and potentially zoonotic schistosome. Overall, the research presented in this thesis used an interdisciplinary, multi-faceted approach to explore the prevalence, distribution and dynamics of S. manson; and Biomphalaria in Lake Victoria. As well as noting the high levels of the disease in human communities, a key element of the research revealed the importance of gastropod biodiversity in predicting Biomphalaria distributions. At the terminal host level, biodiversity was also seen to be important; chimpanzees were observed to be infected with common 'human' forms of S. mansoni, indicating their potential role as reservoirs for the disease, but also demonstrating how wild primate populations, including threatened species such as chimpanzees, can be vulnerable to schistosomiasis as well as other parasitic infections. As such, this Ph.D. research has shed light on a very important avenue of future investigation: the relationship between biodiversity and the spread of infectious diseases, particularly in the context of transmission between humans, non-human primates, and potentially also other reservoir species. While East Africa would be an ideal location to continue this kind of work on schistosomiasis, it also provides the opportunity to extend the research to other parasitic infections, within a broader context of studying the evolution and molecular epidemiology of the interface between medical and veterinary diseases.